Pemetaan Zona Rawan Longsor di Kawasan Agam-Bukittinggi Berbasis Google Earth Engine Menggunakan Teknik Evaluasi Multi-Kriteria - Hilalliyah, Nisful; Namigo, Elistia Liza (Universitas Andalas, 2025)
Landslide vulnerability zone mapping with Google Earth Engine (GEE) has been conducted through a multi-criteria evaluation technique that encompasses scoring, categorization, and overlay of five landslide characteristics in the Agam and Bukittinggi regions of West Sumatra. The criteria utilized are slope, rainfall, land usage, rock type, and soil type. The supervised classification technique employing a random forest classifier is utilized to generate land use categorization maps. The mapping results indicate that the Agam-Bukittinggi region is predominantly characterized by a high to very high degree of landslide susceptibility, encompassing 77,5% (1680,55 km2) of the overall research area, with a medium level of vulnerability. Regions exhibiting high to very high susceptibility to landslides including Tanjung Raya District, Matur District, Malalak District, IV Koto District, Palupuh District, Palembayan District, Tilatang Kamang District, Ampek Angkek District, Kamang Magek District, Banuhampu District, Matur District, Sungai Pua District, Candung District, Baso District and Bukittinggi City. Simultaneously, there exists a 22% risk of moderate landslides in Ampek Nagari District, Lubuk Basung, and Tanjung Mutiara Districtsis.